Electrophysiological characterization of a Cav3.2 calcium channel missense variant associated with epilepsy and hearing loss - Stringer, Robin N; Cmarko, Leos; Zamponi, Gerald W; De Waard, Michel; Weiss, Norbert (Molecular brain, 2023)
T-type calcium channelopathies encompass a group of human disorders either caused or exacerbated by mutations in the genes encoding different T-type calcium channels. Recently, a new heterozygous missense mutation in the CACNA1H gene that encodes the Cav3.2 T-type calcium channel was reported in a patient presenting with epilepsy and hearing loss-apparently the first CACNA1H mutation to be associated with a sensorineural hearing condition. This mutation leads to the substitution of an arginine at position 132 with a histidine (R132H) in the proximal extracellular end of the second transmembrane helix of Cav3.2. In this study, we report the electrophysiological characterization of this new variant using whole-cell patch clamp recordings in tsA-201 cells. Our data reveal minor gating alterations of the channel evidenced by a mild increase of the T-type current density and slower recovery from inactivation, as well as an enhanced sensitivity of the channel to external pH change. To what extend these biophysical changes and pH sensitivity alterations induced by the R132H mutation contribute to the observed pathogenicity remains an open question that will necessitate the analysis of additional CACNA1H variants associated with the same pathologies.
Keywords: Epilepsy; Calcium Channels; vápníkové kanály; mutace; epilepsie; missense mutace; Humans; Mutation; nedoslýchavost; lidé; Mutation, Missense; Hearing Loss